1985
DOI: 10.1007/bf00589250
|View full text |Cite
|
Sign up to set email alerts
|

Series dead space for inert gases in healthy subjects

Abstract: In ten normal subjects, series dead space was determined for six intravenously infused inert gases (SF6, ethane, cyclopropane, fluothane, ether, acetone) from their expired and alveolar concentrations. The method for sampling alveolar gas was based on the criterion of identity of mean alveolar and expired gas exchange ratios. Inert gases were analysed chromatographically. Acetone, the most soluble gas, yielded the lowest dead space, the difference to the other gases being about 4.5%. This is probably due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In figure 2. t.~e e1evated values of the exchange ratio at the beginning of expiration should reflect tpe yery high but non-infinite value of series dead space VA/Q ratio [24].…”
Section: Resultsmentioning
confidence: 98%
“…In figure 2. t.~e e1evated values of the exchange ratio at the beginning of expiration should reflect tpe yery high but non-infinite value of series dead space VA/Q ratio [24].…”
Section: Resultsmentioning
confidence: 98%
“…The arguments contesting this assumption are more diffuse but integrate both experimental and theoretical results. In some experimental studies, the excretion of acetone in relation to ether does not follow the MIGET predicted trend 9,12,55 and dead space as predicted by inert gases decreases as the blood solubility increases 20,41 . Additionally, theoretical studies showed that acetone exchanges predominately within the airways during tidal breathing and these predictions were used to explain inert gas data from humans and dogs 1,56 .…”
Section: Introductionmentioning
confidence: 83%